Model Penguatan Karakter Siswa SD melalui Literasi Finansial, Kreativitas Lingkungan, dan Empati SDN Kedungpapar - Khusnul Khotimah; Fatikhatun Nikmatus Sholihah (PT. Penerbit Riset Sadwa, 2025)
This Community Service Program aimed to strengthen elementary school students’ character through an integrated educational approach encompassing financial literacy, environment-based creativity, and social empathy development. The program was implemented at SDN Kedungpapar, Sumobito District, Jombang Regency, involving elementary students with support from teachers. The methods combined participatory education and hands-on practice (learning by doing), including programs on Saving Habits from an Early Age, Kreasi Alamku through eco-print techniques, and Stop Bullying, Start Empathy. The activity data were analyzed using descriptive qualitative methods based on observations of student participation, behavioral changes, and produced outputs. The findings indicate that saving habit formation effectively enhanced students’ financial awareness and discipline, the use of natural materials improved creativity and environmental awareness, and empathy-based anti-bullying education positively influenced students’ social interactions. This program is relevant to elementary school contexts and has strong potential to be developed as a sustainable community service model integrated into regular school activities.